2016
DOI: 10.1021/acs.nanolett.6b00429
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Nanochannel and Microchannel Resistances

Abstract: Current nanochannel system paradigm commonly neglects the role of the interfacing microchannels and assumes that the ohmic electrical response of a microchannel-nanochannel system is solely determined by the geometric properties of the nanochannel. In this work, we demonstrate that the overall response is determined by the interplay between the nanochannel resistance and various microchannel attributed resistances. Our experiments confirm a recent theoretical prediction that in contrast to what was previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 37 publications
(84 reference statements)
1
75
0
Order By: Relevance
“…Placing the electrodes much closer to the CSI would reduce this effect, as has been noted for simpler geometries29. These findings are also in line with the recent work of Green et al , who demonstrated the importance of the microchannel resistance for simpler microchannel/nanochannel geometries34.…”
Section: Resultssupporting
confidence: 85%
“…Placing the electrodes much closer to the CSI would reduce this effect, as has been noted for simpler geometries29. These findings are also in line with the recent work of Green et al , who demonstrated the importance of the microchannel resistance for simpler microchannel/nanochannel geometries34.…”
Section: Resultssupporting
confidence: 85%
“…It is all because the interfacial layer gets increasingly dominant in narrower channels. [126] Particularly, for a straight CNT with two reservoirs, the resistance can be divided into three parts, namely the entry, the exit, and the developed-flow region. As demonstrated by transport theories, the flow rate can be considered as the ratio of the pressure drop and the resistance.…”
Section: Theoretical Description For Nano-confined Water Flowsmentioning
confidence: 99%
“…in series. [126] Particularly, for a straight CNT with two reservoirs, the resistance can be divided into three parts, namely the entry, the exit, and the developed-flow region. Borg et al [40] proposed a resistance model as…”
Section: Theoretical Description For Nano-confined Water Flowsmentioning
confidence: 99%
“…Passage of an Ohmic current through an ion‐selective medium leads to regions of enriched and depleted salt densities at the opposite interfaces of a permselective nanoporous membrane interfacing bulk electrolyte, a phenomenon known as “ion concentration polarization (ICP)” . This physical principle has been the focus of extensive researches since two decades ago, especially with respect to its potential applications in the microfluidic society, for example, on‐chip seawater desalination where the ICP layer is employed to facilitate a dynamic separation of brine and desalted water streams , or improved biomedical assay by electrokinetic preconcentration of charged analytes at the edge of the ion depletion layer due to a force balance between electrophoresis and electroosmosis .…”
Section: Introductionmentioning
confidence: 99%